Evaluation of factors associated with medical male circumcision in South Africa: A case-control study - Sylvester O. Okhue; Robert J. Mash (AOSIS, 2022)
Background: The World Health Organization recommends medical male circumcision (MMC) to prevent human immunodeficiency virus (HIV). More research is needed in South Africa on factors influencing the uptake of MMC. Aim: To evaluate factors associated with uptake of MMC. Setting: Diepsloot, Johannesburg, South Africa. Methods: An observational case-control study. Cases (men attending a private general practice (GP) offering free MMC) were compared to controls (uncircumcised men attending a local shopping mall) for a variety of demographic, sociocultural and financial factors. Factors were analysed using bivariate and multiple-variable binary forward logistic regression with the Statistical Package for Social Sciences. Results: There were 350 cases and 350 controls. Four factors were associated with the uptake of MMC: being a student (adjusted odds ratio [AOR]: 6.29, 95% confidence interval [CI]: 2.29-17.26), attending a mainline Christian denomination (AOR 2.85, 95% CI: 1.39-5.78), speaking an African language other than Zulu (range of AORs: 2.5-6.8, p 0.05) and being South African (AOR: 2.50, 95% CI: 1.58-3.96). MMC was associated with feeling susceptible to HIV, seeing it as a serious health problem and being encouraged by partners. Men who were sterilised, not sexually active and without symptoms of a sexually transmitted infection felt less susceptible. Other barriers included the pain of the procedure, indirect costs, anticipated impact on sexual activity, lack of information, cultural beliefs, embarrassment and access to health services.